Efficient Synthesis of Substituted 2-Nitrochalcone Derivatives - Alam Yair Hidalgo; Quirino Torres-Sauret; Carlos Ernesto Lobato-García; Miguel Ángel Vilchis-Reyes; Abraham Gómez-Rivera; Oswaldo Hernandez-Abreu; Nancy Romero-Ceronio (Chemistry Proceedings, 2024)
Organic synthesis plays a fundamental role in medicinal chemistry, allowing the production of compounds with desirable pharmacological properties. In this context, new synthesis methods, such as the use of ultrasound, are continuously being explored to improve the efficiency and sustainability of these processes. In this work, the synthesis and structural characterization of 2-nitrochalcone derivatives substituted with electron-withdrawing (fluoro) and electron-donating (methoxy) groups in the three isomeric positions of the B ring via nuclear magnetic resonance and ultrasound are presented; both a conventional method and a nonconventional ultrasound-assisted method are used. The results show that both methodologies are effective for obtaining these compounds, but the conventional method presents some additional advantages in the case of these nitrochalcones, such as shorter reaction times and better reaction yields.